EFEKTIFITAS PENGGUNAAN M-WEBQUEST TERHADAP KEMAMPUAN MEMBACA BAHASA INGGRIS SISWA SMAN DI PEKANBARU - Hadriana ' (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2014)
This is a Quasi-experiment research used to determine theeffectiveness of using M-WebQuest towards reading comprehension achievementof private senior high school students in Pekanbaru - Riau. Sampel of this researchinvolved 260 students that consisted of 130 students for treatment group and 130students for control groups. This involved eight classes from two senior highschools in Pekanbaru - Riau Indonesia. Data were collected using questionnairesand test on students’ reading comprehension achievement. The test was analyzedusing ANATESV4 and SPSS 19.0. The analysis of the data obtained throughquasi-experiment reveals that there is significant difference between students’reading comprehension achievement taught by using M-WebQuest compared tothose who are taught conventionally. The study implication shows that the teachershould use various approaches in teaching and learning process. Using M-WebQuest is one of the way and it can improve students’ reading comprehensionachievement.Keywords: M-WebQuest, reading comprehension achievement